An Appraisal Analysis of The Text of President Joko Widodo’s Speech - Simanjuntak, Faido Marudut Pardamean (PT FORMOSA CENDEKIA GLOBAL, 2024)
The appraisal system that focuses on attitude types, is elucidated in this research. Appraisal represents an expansion of the Systemic Functional Linguistics theory in the area of interpersonal meaning, introduced by Martin and White. This study employs qualitative research coupled with discourse analysis (DA) methodologies. The primary focus of this research is the analysis of President Joko Widodo's speech text. at the send-off of the Indonesian Team to the XXXIII Paris 2024 Olympic Games. This research uses document analysis as a data collection technique. The research results showed that there were 10 attitude systems consisting of 2 positive affects, 5 positive judgments, 2 positive appreciations, and 1 negative appreciation. It is hoped that the athletes will bring home honor and pride for Indonesia with the positive attitude of President Joko Widodo, which demonstrates his full support.